SLANG WORDS ANALYSIS IN SKIN MOVIE - Rini Tarihoran; Eka Wilany (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2021)
Slang is confidential informal English, which is created and used by a society. This study discusses about an analysis of slang in the Skin movie. The purpose of this study is to find the type of slang and the reason why people / society used slang words in daily conversation. The source of the data was taken from the script of Skin movie. Skin movie was classified as a biographical drama movie released on 2018 in Tokyo and directed by Guy Nattiv. The research design used in this study is a descriptive qualitative research with a document or content analysis as the research type. This thesis is described one by one word or phrase of slang found from the Skin movie by using dictionaries and theory related to slang. From the analysis, there are fifty-two slang words found and one type of slang used, they were society slang. Then the reasons found and used in this study are at least seven types. There were in sheer high spirits, to express humour, to be different, to express surprising / shocking, to be brief and concise, to express refusal / rejection, and to show friendliness. This study highly expected to give contribution for the readers to know about slangs clearly. It can help the readers speak English fluently. Then, it can also be expected to enrich the new English vocabulary used in daily conversation.